Information Technology-Based Medical Record Governance For Cancer Classification With The Waterfall Method - Rahmawati, Risa Luthfiani; Abdussalaam, Falaah; Sari, Irda (Universitas Negeri Padang, 2024)
Information technology can help improve the quality of medical record management. Information technology-based medical record management can help improve the efficiency, accuracy and accessibility of medical records. The aim of this research is to build an information technology-based medical record management system for cancer classification using the waterfall method. This research uses a system development research method using the waterfall method. The data collection techniques used were observation, interviews and literature study. The data that has been collected is then analyzed qualitatively. The research results show that an information system designed specifically for patients who register directly makes it easier for officers to separate patients who register online from those who register in person. This system allows officers to report information quickly and accurately, and to be better integrated in quality improvement and hospital accreditation.